Effect of modified atmosphere packaging on overall appearance and nutraceutical quality of pot marigold held at 5 °C. (August 2020) - Fadda, Angela; Palma, Amedeo; Azara, Emanuela; D'Aquino, Salvatore
Graphical abstract: Highlights: MAP preserved the quality of calendula petals for ten days at 5 °C. Continuous and micro-perforated films kept flowers' weight, freshness and color. MAP delayed total phenols' concentration decrease over storage. Micro and macro perforated films determined an increase of β-carotene content. Micro-perforation is a good compromise between in package RH and film permeability. Abstract: The effectiveness of passive modified atmosphere packaging (MAP) on chemical and quality properties of calendula flowers was studied during ten days of storage at 5 °C. Weight loss of flowers wrapped with continuous and micro-perforated-films (2–3%), was significantly lower than control (unwrapped flowers) (about 30%) and those wrapped with macro-perforated film (about 7%). At the end of storage unwrapped flowers were judged unmarketable being severely wilted and shriveled, while all packaged ones were still fresh and marketable. On day 10, the fructose concentration of control flowers decreased by 74%. Continuous and micro-perforated films delayed the decline of fructose concentration over storage. Sucrose concentration decreased with storage in control flowers, while in continuous film wrapped flowers it increased. After 10 d of storage, the total phenols' concentration of all packaged flowers was significantly higher than control and similar to the initial value (2.58 ± 0.02 g 100 g −1 d.w.). Thirteen carotenoids were identified by HPLC-MS. The initial β carotene concentration (65.72 ± 0.09 mg 100 g −1 d.w.) did not change in flowers wrapped with macro- and micro-perforated films, in contrast to the other treatments. Lycopene concentration strongly decreased in control flowers, while minor losses occurred in packaged ones. Laser micro-perforated film, being a good compromise between humidity retention inside the packages and the permeability of the film, seems to be the best choice to extend the storage life of calendula flowers.